(untitled) (Journal of the College of Basic Education, 2023)
The school of psychoanalysis is one of the important schools that made a significant contribution to the study of human creativity. Psychologists attach great importance to the study of poetic creativity, as it is a sincere emotional state that expresses the psychological suffering of the creator as well as its distinct impact on the psyche and thought of the recipient. A poet or critic of Arabic poetry, its rulings are from psychological visions related to the impact of poetry on its author and on the recipient, just as poetry has an effect on opposing souls, and the ability to reformulate feelings. That is, who enters the heart as soon as the listener receives it.